HUBUNGAN TINGKAT KETAHANAN PANGAN, POLA MAKAN DAN PERILAKU SEDENTARI DENGAN KEJADIAN OBESITAS PADA SISWA SMP DI KABUPATEN BADUNG - Triayuni, Anak Agung Sagung Anom; Utami, Ni Wayan Arya (ARCHIVE OF COMMUNITY HEALTH; Vol 12 No 1 (2025): April 2025, 2025)
ABSTRACT Junior high school students, classified as adolescents, are susceptible to obesity, which can affect their physical growth and development. Obesity is influenced by multi-factors, including household food security, dietary patterns, and sedentari habits. This research aims to establish connections between household food security, eating behaviors, sedentari behavior, and the prevalence of obesity among junior high school students in Badung Regency. Employing a quantitative method with a cross-sectional design, the study employs multistage random sampling involving 193 students. It examines the socio-demographic features of students and families, household food security, dietary diversity, macronutrient intake, and sedentari behavior. Analyzing the collected data using univariate and bivariate techniques, the findings reveal significant associations between energy intake (p=0.003) (OR=3.14), protein intake (p=0.000) (OR=3.70), sedentari behavior (p=0.005), and obesity risk among junior high school students. Conversely, household food security (p=0.62) (OR=0.31), carbohydrate intake (p=0.70) (OR=0.87), and fat intake (p=0.11) (OR=0.40) exhibit no notable links. These outcomes underscore the necessity for more robust strategies that encompass both nutritional education initiatives and the cultivation of healthy eating habits, involving students and parents. The ultimate goal is to stimulate active student involvement in appropriate nutritional choices and physical engagement, both within and beyond the school premises. Keyword: Adolescent, Food Security, Dietary Habit, Sedentari Behaviour, Badung